Application of hart concentrator to save the number of input analogue channel usage in PLC PAC system on SCADA cimplicity - Anton Hidayat; Reza Nandika; Anton Anton; Nadia Alfitri; Alfred Trinanda (Politeknik Negeri Padang, 2023)
The types of inputs and outputs of a control system that exist today are quite varied with their respective advantages and disadvantages that can be adapted to existing needs. So with the complexity of the system, the price is also very expensive. As one option to overcome this problem is to utilize Highway Addressable Remote Transducer (HART) data through the application of the HART Concentrator System (HCS). HART data has four variables, namely Primary Value (PV), Secondary Value (SV), Third Value (TV) and Fourth Value (FV). All this data can be sent simultaneously to HCS and collected. Then the data on the HCS will be sent via RS485 serial communication to the Modbus Gateway TCPIP. At this Modbus TCPIP gateway, Modbus data can be sent via an Ethernet network so that it can be accessed flexibly by SCADA.